S11-2: Children’s Voices and Roles in a Whole-System Physical Activity Intervention in Bradford: JU:MP (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This paper presents findings from the process evaluation of JU:MP, a whole-system intervention designed to increase physical activity among children aged 5–14 in Bradford, United Kingdom. The paper explores two interlinked aspects of children’s and families’ involvement: (1) their experiences and perceptions of the intervention and (2) the extent and nature of children’s involvement in JU:MP’s design and delivery.Method: The first strand draws on qualitative data from longitudinal dyad interviews with families (7 families, 19 interviews at three time points) and focus groups conducted with children (12 focus groups, n = 93) and parents (7 focus groups, n = 17) across two time points. The second strand, which interrogates how children’s voices were embedded in intervention’s design and delivery, draws on four focus groups with children, two focus groups with research and implementation staff, and secondary analysis of over 60 interviews and focus groups with community stakeholders.Results: The process evaluation from the perspective of families highlights three themes: children’s and families’ awareness of the intervention, children’s enthusiastic engagement with various elements of JU:MP, and impact on behaviour change. Participants demonstrated high acceptance of the intervention elements provided both in school and out-of-school settings. The impact is most evident on children’s motivation, socialisation, and strengthening of community ties and increased opportunities for PA. The analysis of children’s involvement reveals the shifting and evolving nature of child consultation and involvement across programme neighbourhoods, ranging from informal feedback to more structured co-design mechanisms. Although there was strong initial motivation to involve children, systemic barriers, such as time constraints, ethical considerations, and misalignment with strategic priorities, limited their involvement.Conclusion: Listening to children ensures the acceptability, effectiveness, and sustainability of interventions. Practitioners and researchers who aspire to embed children’s voices in PA interventions would do well to design flexible engagement structures, transparent processes for managing power dynamics, and long-term investment in community relationships.Support/Funding source: This study was supported by Sport England’s Local Delivery Pilot – Bradford; weblink: https://www.sportengland.org/campaigns-and-our-work/local-delivery. Sport England is a non-departmental public body under the Department for Digital, Culture, Media and Sport.Keywords: Children, physical activity, intervention, process evaluation, consultation